Construction and Brain Validation of circRNAs-miRNAs-mRNAs Regulatory Axis in Early-Onset Schizophrenia - Zhang X; Li Z; Li R; Wang X; Liu H; Du X; Gao Y; Liu S; Xu Y (Neuropsychiatric Disease and Treatment)
Xiuping Zhang,1,2,* Zexuan Li,3,4,* Ruiting Li,5,* Xinxia Wang,1 Huanghui Liu,1 Xinzhe Du,1,4 Yao Gao,1,4 Sha Liu,1,4 Yong Xu1,3,4 1Department of Psychiatry, Shanxi Medical University, Taiyuan, People’s Republic of China; 2Department of Neurology, Second Hospital of Shanxi Medical University, Taiyuan, People’s Republic of China; 3Department of Psychiatry, The Eighth Affiliated Hospital, Sun Yat-sen University, Shenzhen, People’s Republic of China; 4Shanxi Key Laboratory of Artificial Intelligence Assisted Diagnosis and Treatment for Mental Disorder, First Hospital of Shanxi Medical University, Taiyuan, People’s Republic of China; 5Department of Pain Management, Taiyuan Central Hospital, Taiyuan, People’s Republic of China*These authors contributed equally to this workCorrespondence: Yong Xu, Department of Psychiatry, Shanxi Medical University, Taiyuan, People’s Republic of China, Email xuyongsmu@vip.163.com Sha Liu, Department of Psychiatry, Shanxi Medical University, Taiyuan, People’s Republic of China, Email liusha1984114@163.comBackground: High rates of misdiagnosis and missed diagnosis of schizophrenia highlight the urgent need for objective diagnostic indicators. Previous studies showed that microRNAs and circular RNAs are potential candidates. This study aimed to investigate the regulatory patterns and brain validation of circular RNAs-microRNAs-messenger RNAs in early-onset schizophrenia.Methods: Differentially expressed circular RNAs and microRNAs were identified in blood samples from 32 patients with early-onset schizophrenia and 29 healthy controls. Circular RNAs were confirmed to possess circular structures. The interactions among circular RNAs, microRNAs, and messenger RNAs were examined using dual-luciferase reporter assays. The circRNA of interest was knocked down and overexpressed in the SH-SY5Y cell line to evaluate changes in gene expression. Brain validation of the axis was performed in animal models.Results: Compared with healthy controls, 8 circular RNAs and 3 microRNAs exhibited significant and stable differential expression, with 6 of the 8 circular RNAs confirmed to have circular structures. Hsa-circ-0000713 was identified as containing the response element for hsa-miR-370-3p, which targeted ANK3 and MGLL. Hsa-circ-0000713 acted as a sponge, mitigating the inhibitory effects of hsa-miR-370-3p on ANK3 and MGLL. The expression patterns of this axis in the prefrontal cortex were consistent with those observed in peripheral blood samples from clinical patients.Conclusion: This study identified a specific multi-molecular axis in early-onset schizophrenia, wherein hsa-circ-0000713 functioned as a sponge to reduce the inhibitory effects of hsa-miR-370-3p on ANK3 and MGLL. This axis may contribute to the pathogenesis of early-onset schizophrenia by mediating abnormalities in prefrontal cortex development.Keywords: early-onset schizophrenia, circRNAs, miRNAs, mRNAs, multi-molecular axis, brain validation